1998
DOI: 10.1063/1.366952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the substrate on growth and magnetoresistance of La0.7Ca0.3MnOz thin films deposited by magnetron sputtering

Abstract: Off-axis radio frequency magnetron sputtering was employed to grow La0.7Ca0.3MnOz (LCMO) thin films onto three different types of substrates. The substrate strongly influences the structure and the colossal magnetoresistance effect of the obtained films. Single-crystalline thin films were prepared on LaAlO3 (100) substrates, showing a low value of residual resistivity and a metal–insulator transition at a temperature of up to Tpeak=290 K. The latter value of the transition temperature is one of the highest rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 26 publications
4
51
0
2
Order By: Relevance
“…We determined the c-axis lattice parameter for F and AF films at 0.385 ± 0.002 nm and 0.376 ± 0.002 nm, respectively [15]. Our results revealed that the F film agrees well with the bulk value obtained for this type of manganite (0.3867 nm) [16], whereas the AF film exhibits a larger deviation with respect to other reports (0.381 nm). Similarly, the substrate lattice parameter was estimated from the (00l) Bragg-Peak position observed, obtaining approximately 0.389±0.002 nm for SrTiO 3 , which is consistent with the expected substrate lattice parameter of 0.390 nm [17].…”
Section: Structural Characterizationsupporting
confidence: 87%
“…We determined the c-axis lattice parameter for F and AF films at 0.385 ± 0.002 nm and 0.376 ± 0.002 nm, respectively [15]. Our results revealed that the F film agrees well with the bulk value obtained for this type of manganite (0.3867 nm) [16], whereas the AF film exhibits a larger deviation with respect to other reports (0.381 nm). Similarly, the substrate lattice parameter was estimated from the (00l) Bragg-Peak position observed, obtaining approximately 0.389±0.002 nm for SrTiO 3 , which is consistent with the expected substrate lattice parameter of 0.390 nm [17].…”
Section: Structural Characterizationsupporting
confidence: 87%
“…The deposition procedure used for NdBaCo 2 O 5+x films was close to that developed for the epitaxial growth of La 0.7 Ca 0.3 MnO 3 and La 0.7 Sr 0.3 MnO 3 thin films [11,12]. The chamber pressure was the same p = 10 Pa, while the substrate temperature T sub was modified over the range from 580…”
Section: Methodsmentioning
confidence: 99%
“…It was shown in our previous work [5,6] that the deposition temperature and mismatch of the lattice constants between the manganite film and the substrate have a crucial influence on the film growth. For a very low lattice mismatch the obtained films are single crystalline independent of employed deposition technique.…”
Section: Mr = [(R(h) -R(0)]/r(0)mentioning
confidence: 99%
“…Recently the colossal magnetoresistance (CMR) phenomenon has attracted much attention as both a fundamental research and an applied science challenge [1]. It has been demonstrated that low-field magnetoresistance (LFMR) effects have an important influence in bulk polycrystalline materials [2,3], polycrystalline thin films [4][5][6], and thin films with reduced epitaxy [7,8]. It was established that the control of crystallinity perfection of thin manganite films, such as epitaxial strain or granularity, could be utilized for tuning of their MR properties, especially of LFMR [6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation